A comparative study of three diagnostic criteria for atopic dermatitis - Weijia ZHAO; Yuzhen LI (editoiral office of Journal of Diagnosis and Therapy on Dermato-venereology, 2023)
Objective To compare the specificity, sensitivity, variability and consistency among three different diagnostic criteria for atopic dermatitis (AD) in subjects with and without AD. Methods We retrospectively analyzed patients with AD initially diagnosed according to the Hanifin Rajka criteria at our clinic between September 2020 and October 2021. Demographic characteristics, clinical manifestations and the results of laboratory tests were used to analyze the sensitivity and specificity of Williams criteria, Zhang's criteria/Chinese criteria and Chinese diagnostic criteria for childhood AD. Patients with other dermatological diseases visiting our clinic during the same period were used as controls. The sensitivity and specificity of the three diagnostic criteria were compared using McNemar's test, while Kappa values were used to determine the consistency of the diagnostic criteria. Results One hundred and ten patients with AD and 91 patients without AD were included in this analysis. The highest sensitivity and lowest specificity were Chinese diagnostic criteria for childhood AD (83.6%, 59.3%). Both Zhang's criteria/Chinese criteria and Williams criterion displayed the highest specificity (90.1% for both). Both positive and negative predictive values (90.2%, 75.2%) were higher for Zhang's criteria/Chinese criteria than the others. The Williams criteria exhibited the highest false negative rate (29.1%), while the highest false positive rate was found for the Chinese diagnostic criteria for AD in children (40.7%). The Zhang's criteria/Chinese criteria displayed the highest Youden index and Kappa coefficient, with a Kappa coefficient of 0.645 (95% CI: 0.541-0.748, P<0.05). Conclusion The statistical advantage of Zhang's criteria/Chinese criteria is slightly greater than that of Williams criteria and Chinese diagnostic criteria for AD in children, which is in high agreement with the gold standard.